Portosystemic shunting and persistent fetal vascular structures in aryl hydrocarbon receptor-deficient mice - Lahvis, Garet P. (The National Academy of Sciences, 2000)
A physiological examination of mice harboring a null allele at the aryl hydrocarbon (Ah) locus revealed that the encoded aryl hydrocarbon receptor plays a role in the resolution of fetal vascular structures during development. Although the aryl hydrocarbon receptor is more commonly studied for its role in regulating xenobiotic metabolism and dioxin toxicity, a developmental role of this protein is supported by the observation that Ah null mice display smaller livers, reduced fecundity, and decreased body weights. Upon investigating the liver phenotype, we found that the decrease in liver size is directly related to a reduction in hepatocyte size. We also found that smaller hepatocyte size is the result of massive portosystemic shunting in null animals. Colloidal carbon uptake and microsphere perfusion studies indicated that 56% of portal blood flow bypasses the liver sinusoids. Latex corrosion casts and angiography demonstrated that shunting is consistent with the existence of a patent ductus venosus in adult animals. Importantly, fetal vascular structures were also observed at other sites. Intravital microscopy demonstrated an immature sinusoidal architecture in the liver and persistent hyaloid arteries in the eyes of adult Ah null mice, whereas corrosion casting experiments described aberrations in kidney vascular patterns.